Estudo das imagens simbólicas nas toadas de bumba meu boi de Donato Alves: uma contribuição para a educação - Coelho, Ivandro de Souza (2016)
This study aims to make a symbolic interpretation of the representations in the "bumba meu boi" songs of the singer, born in the Brazilian state of Maranhão, Donaldo Alves. This analysis is made considering the four natural elements: water, air, earth and fire. Its theoretical fundament is based on the Abstraction Theory perspectives of Gaston Bachelard and Gilbert Duran. The study attempts to understand the recurrent symbols in Donato Alves' work as well as its contributions to a humanizing education. It is a research anchored to a comprehensive hermeneutic view and one that renews the sense, as it deals with the plysemic symbols represented in human creations. Therefore, this study is based on a holistic paradigm which values the unity of knowledge, of science and of men, as well as considers the complexity of the subject, understanding these abstractions as constituting and organizing elements of society. Regarding data collection, this study considers the reading/listening of Donato Alves' songs and other works connected to the subject as well as the experience of a workshop at CE Raimundo Araújo in Chapadinha-MA. A qualitatitive approach was chosen for the research, in a comprehensive perspective, which contemplates a selection of texts and literary representations analysed in their contexts to provide a more accurate interpretation of the phenomenon in case. It is concluded that folk literature and abstraction, once experienced at school through literary symbols, allow students (reader/listener) to develop their imagination, creativity and emotions, giving them tools to understand themselves and others. This process accurs through dialogue, in a sensitive way, contributing thus to a humanizing education.